Evaluation of the Out-Programme One Year Teaching Practice of Final Year Students (Mentees) of St. Joseph’s College Of Education-Bechem - Amanfo, Samuel Owusu (2012)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of MASTER OF ARTS IN ART EDUCATION